LEGAL BASIS OF SOCIAL PARTNERSHIP FOR THE PROTECTION OF HUMAN RIGHTS IN THE NEW UZBEKISTAN (TAMADDUN NURI JURNALI, 2024)
This article analyzes issues such as the legal basis of social partnership for the protection of human rights in the new Uzbekistan and the coverage of human rights and freedoms.